2019
DOI: 10.1016/j.fm.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry sanitization by peracetic acid washing and its effect on fruit quality

Abstract: Washing time was irrelevant to reduce epiphytic microbiota and L. innocua populations. Aerobic mesophylls were reduced similarly by peracetic acid (PA) and NaClO washes. All PA washing treatments reduced the L. innocua populations by 4 log units. L. innocua counts in PA washing solutions were 4-log units lower than they were in control water.  Sanitization had no relevant impact on quality nor on biochemical characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
(37 reference statements)
2
45
0
1
Order By: Relevance
“…These results indicate that the proposed sanitizers are more efficient at controlling this microbial group than the conventional treatment. Nicolau-Lapena et al [26] observed a different result for yeasts and molds: treatment with chlorine compounds and peracetic acid reduced contamination in washing water, but no differences were observed in strawberries.…”
Section: Effect Of the Sanitization Treatments On Natural Microbiotamentioning
confidence: 97%
See 3 more Smart Citations
“…These results indicate that the proposed sanitizers are more efficient at controlling this microbial group than the conventional treatment. Nicolau-Lapena et al [26] observed a different result for yeasts and molds: treatment with chlorine compounds and peracetic acid reduced contamination in washing water, but no differences were observed in strawberries.…”
Section: Effect Of the Sanitization Treatments On Natural Microbiotamentioning
confidence: 97%
“…Gurtler, Bailey, Jin and Fan [45] obtained similar results in the evaluation of the effects of 1% acetic acid solution treatment for 2 min on seven strains of E. coli O157:H7 on inoculated strawberries. Nicolau-Lapena et al [26] artificially inoculated Listeria innocua in strawberries and observed that all sanitizantion treatments with peracetic acid reduced its number by at least 4 log CFU/g, except for the 20 mg/L treatment for 1 min.…”
Section: Effect Of the Treatments On Escherichia Coli Atcc 11229 Adhementioning
confidence: 99%
See 2 more Smart Citations
“…However, such practices cause later effects of bio-accumulation of pesticides through the food chain (Kin and Huat, 2010); thus, the sanitisation process is needed upon harvesting to get rid of any pesticides residue. Contamination of fresh strawberries may happen due to insects, soil, water or improper handling, either during the pre-harvest or postharvest stages, thus sanitisation is a crucial first approach for inactive spoilage bacteria to preserve the freshness of products (Nicolau-Lapena et al, 2019). A prior study by Kin and Huat (2010) on sanitisation of strawberry fruits collected at the Malaysian Agricultural Research and Development Institute (MARDI), Cameron Highlands with different sanitising solutions of acetic acid, sodium carbonate, sodium chloride and solely tap water showed that acidic solutions of 5 to 10% acetic acid in tap water removed around 44 to 70% pesticide residues in strawberries after soaking for 10 to 30 minutes and dried overnight.…”
Section: Sanitisation Of Postharvest Strawberriesmentioning
confidence: 99%